O estudo de áreas vulneráveis a enchentes : uma ferramenta na mitigação de impactos. O caso de São José do Rio Preto-SP - Ártico, Beatriz de Carvalho (2013)
Over past years, in the period of greatest rainfall - between december and march the cities suffer from floods. There are various motives for the urban floods, including the changes in the hydrological cycle and the disordered process of urban land use and occupation. Floods cause impacts to the population subject to the phenomenon, whose mitigation is fundamental and is based an action that balances urban development with environmental conditions. The present work aims to identify the main factors which act directly or indirectly in floods from the perspective of the areas vulnerable to flooding, with case study in the city of Sao Jose do Rio Preto-SP. From the analysis of the literature review were selected four parameters related to the areas vulnerable to flooding: the use and occupation of urban land, the river basin, the urban drainage, and the vulnerability. A method of evaluation of areas with the main features to be parsed assigning scores to the same, with the intention of quantifies and qualifies them. As a result were obtained a diagnoses form the selection area with their respective scores, degree of vulnerability, recommendations and suggestions, as well as map overview and representation schematic of the area.